Growth Gains from Trade - Sugata Marjit; Anwesha Basu; C. Veeramani (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper revisits the relationship between international trade and economic growth. We measure trade openness indices separately with respect to intermediate inputs and final goods and find that it is the former which turns out to be significant in explaining growth gains from trade. Using sectoral level data from WORLD KLEMS Database on industrial productivity and output and global input output tables to construct the measures of trade openness, our empirical analysis covering 21 countries, 30 industries and 15 years reveals that trade openness in terms of intermediate and capital goods lead to economic growth. Openness in terms of final consumer goods turns out to be insignificant in most specifications. We also estimate traditional cross country growth regressions where we use trade data to construct the two trade openness indices for 174 countries. Here again, we find that it is import of intermediate and capital goods that results in real per-capita income growth. Our empirical results are in line with our theoretical model, where we show, without imposing any transplanted structure in our model that trade in intermediate goods directly leads to higher growth relative to autarky as opposed to trade in final goods.
Keywords: C10; F10; O40; 330; trade; openness; growth; gains from trade; per capital income